Eksplorasi Penerapan Digital Community Oleh PT Ace Hardware Indonesia: Studi Kasus Meningkatkan Interaksi dan Loyalitas Kota Banjarmasin - Linda Linda; Melisa Agustina; Maisarah Maisarah; Gita Medina; Nor Anisa (Universitas Methodist Indonesia, 2025)
This study aims to analyze the implementation of digital community strategies by PT Ace Hardware Indonesia to enhance customer interaction and loyalty through a case study in Banjarmasin City. In the digital era, an active customer community has become a critical strategic asset for companies to build long-term relationships with consumers. This research employs a qualitative approach through in-depth interviews with company representatives to explore how digital platforms, such as mobile applications, social media, and loyalty programs, are effectively utilized. The findings indicate that PT Ace Hardware Indonesia adopts interactive content campaigns, exclusive discounts, and personalized features to boost customer engagement. Additionally, the established digital community enables customers to discuss, share experiences, and provide valuable feedback, indirectly strengthening brand loyalty. With consistent implementation, the company successfully expands its market share while creating an enhanced customer experience. This study provides practical insights for other companies seeking to integrate digital community strategies as part of their marketing efforts and customer relationship management in a technology-driven environment.